The effect of Silymarin on glycemic control of type II diabetes: A double blind randomized clinical trial - H Fallah Huseini; B Larijani; B Raajabipour; R Heshmat (Institue of Medicinal Plants, ACECR, 2005)
Background: Silymarin is a free radical scavenger and cell membrane stabilizer, that may reduce insulin secretion without increasing blood-glucose concentration and this combination of effect could be useful in states of hyperinsulinaemic hyperglycemia, such as non-insulin-dependent diabetes. Objective: The aim of this study was to analyze the effect of silymarine on glycemic control of type II diabetes. Material and Methods: A 4-month randomized clinical trial study was conducted in two-well-matched groups of type II diabetes. One group (n=30) received 750mg silymarin into divided three doses per day plus standard therapy, while the control group (n=30) received standard therapy and placebo. At the beginning and the end of the study HbA1C, FBS, serum Insulin, SGOT and SGPT were measured. Results: The mean age of patients was 53.5 ±6.2 years and the mean duration of disease was 9.6±5.9 years. There was a significant decrease in fasting blood glucose (FBS) levels from 155± 46 mg/dl to 133±39mg/dl (p=0.001), also HbA1C levels from 7.82±2.01 to 6.78±1.05 (p=0.001). There was a significant decrease in SGOT (p=0.008) and SGPT (p=0.0001) levels, after 4-months treatment in the silymarin group. In addition, there was a non significant decrease in Blood Pressure and weight in this group. Conclusion: The results show that treatment with silymarin reduces the FBS and HbA1c. The effect of silymarine may be due to Antioxidative effects, reduction of the lipoproxidation of cell membranes and other unknown effects.